Standalone solar PV system for grey water recycling along with electric load for domestic application. Issue 5 (3rd September 2021) - Prajapati, Sandhya; Fernandez, E.
ABSTRACT: Water scarcity issue is dominatingly seen in the big cities and continuously increasing in the past years. The proposed system investigates that the standalone solar PV, which is used for the household electric load, can also be used for the grey water recycling with the optimised system design. The paperwork not only saves the recycled grey water but also fulfil the residential electric load. The proposed system further compared with the conventional system. The result obtained shows that the system saves 14, 721.5 gallons' water per year; also the cost of the proposed system is less as compared to the conventional system.